MORPHOLOGY OF ISCHEMIC INJURY OF LIVER ALLOGRAFT ACCORDING TO BIOPSIES RESEARCH - L. V. Shkalova; M. G. Minina; N. P. Mogeiko; I. M. Iljinsky; Y. G. Moysyuk; O. M. Tsirulnikova; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2010)
The aim of our work is to develop diagnostic criteria of liver ischemic injury according to needle biopsies of liver allograft using light microscopy. We studied 45 zero liver biopsies from cadaver donors with diagnosed brain death and 16 needle biopsies of liver allograft from 12 recipients 1 hour up to 1 month after operation. Grading to three stages of ischemic injury in liver allograft is based on clinical and morphological criteria. Ischemic injury of liver allograft is an acute alterative-inflammatory process i.e. there are hepatocyte degeneration and necrosis with following inflammation (exudation with edema, hemorrhage, neutrophil infiltration). In case of favorable outcome ischemic injury of liver allograft is a reversible process.